1999
DOI: 10.1097/00005392-199909010-00094
|View full text |Cite
|
Sign up to set email alerts
|

“Skin-CNS-Bladder” Reflex Pathway for Micturition After Spinal Cord Injury and Its Underlying Mechanisms

Abstract: The cross-wired somato-autonomic bladder reflex is effective in initiating bladder contractions and coordinated voiding in cats with an intact neuraxis and can also induce bladder contractions after acute transection of the lumbar spinal cord. The new pathway is mediated by cholinergic transmission involving both nicotinic and muscarinic receptors. It is concluded that somatic motor axons can innervate bladder parasympathetic ganglion cells and thereby transfer somatic reflex activity to the bladder smooth mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 14 publications
3
56
0
5
Order By: Relevance
“…End-to-end anastomosis of injured ventral roots to adjacent intact ventral roots has resulted in bladder improvements in rats (Xiao and Godec, 1994), cats (Carlsson and Sundin, 1968;Vorstman et al, 1986;Xiao et al, 1999), canines (Ruggieri et al, 2004), and humans (Carlsson and Sundin, 1980;Xiao et al, 2003). This procedure requires an additional lesion to uninjured neurons and a shift in function by the originally uninjured neurons to now reinnervate a new target.…”
Section: Reinnervation Of the Lut Function After Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…End-to-end anastomosis of injured ventral roots to adjacent intact ventral roots has resulted in bladder improvements in rats (Xiao and Godec, 1994), cats (Carlsson and Sundin, 1968;Vorstman et al, 1986;Xiao et al, 1999), canines (Ruggieri et al, 2004), and humans (Carlsson and Sundin, 1980;Xiao et al, 2003). This procedure requires an additional lesion to uninjured neurons and a shift in function by the originally uninjured neurons to now reinnervate a new target.…”
Section: Reinnervation Of the Lut Function After Injurymentioning
confidence: 99%
“…This procedure requires an additional lesion to uninjured neurons and a shift in function by the originally uninjured neurons to now reinnervate a new target. Furthermore, the intact dorsal roots create a new somatic-CNS-bladder reflex circuitry, whereby scratching the skin in specific dermatomes may elicit bladder contractions (Xiao et al, 1999(Xiao et al, , 2003. Although nerve-to-nerve anastomosis requires peripheral nerve regeneration, our repair model differs in that CNS regeneration is also necessary for reestablishment of the micturition circuitry by the originally injured neurons without inflicting any additional lesions to uninjured neurons.…”
Section: Reinnervation Of the Lut Function After Injurymentioning
confidence: 99%
“…Xiao and associates established the skin-central nervous reflex pathway system for the treatment of neurogenic bladder through end-to-end anastomosis of left L4/L5 ventral VR (somatic nerves) to L6/S2 VR( autonomic nerve) in rats and cats, respectively [46,47]. Peters [48] and Xiao [49,50] demonstrated that the skin-central nervous reflex pathway system following endto-end anastomosis of L5 VR (somatic nerves) to S2/S3 VR (autonomic nerve) could recover controllable voiding function in the clinical trial.…”
Section: The Advantages Of Terminolateral Neurorrhaphy Of Autonomic-smentioning
confidence: 99%
“…Restoring normal voiding function in spinal cord injury (SCI) patients is a great challenge for neurology [1] . Researches on restoring functional micturition have been mainly focused on electrical stimulation for decades and with progresses, but it is not yet the definitive solution for majority of SCI patients [2] .…”
Section: Introductionmentioning
confidence: 99%